Strategies for Improving Tensile Ductility of Bulk Nanostructured Materials - Zhao, Yonghao; Zhu, Yuntian; Lavernia, Enrique J. (Advanced engineering materials, 2010)
The low ductility that is consistently associated with bulk nanostructured (NS) materials has been identified as perhaps the single most critical issue that must be resolved before this novel class of materials can be used in a wide variety of applications. Not surprisingly, a number of published studies, published mostly after 2000, identify the issue of low ductility and describe strategies to improve ductility. Details of these strategies were discussed in review papers published by Koch and Ma in 2005 and 2006, respectively.15,16 In view of continued efforts and recent results, in this paper we describe progress in attempting to address the low ductility of NS materials, after 2006. We first analyze the fundamental reasons for the observed low ductility of bulk NS materials, and summarize early (prior to 2006) attempts to enhance the ductility of bulk NS materials, which often sacrificed the strength. Then, we review recent progress in developing strategies for improving the tensile ductility of bulk NS materials, which involve mainly microstructure modifications, after 2006. Different from early efforts, these new strategies strive to increase the tensile ductility while increasing/maintaining the strength simultaneously. In addition, the influence of tensile testing conditions, including temperature, strain rate, tensile specimen size and geometry, and strain measurement methods, on tensile ductility of NS materials will also be reviewed. Finally, we identify several issues that will require further, in depth analysis in the future. This paper reviews recent progress in developing strategies for improving the tensile ductility of bulk NS materials, which involve mainly microstructure modifications, after 2006. Different from early efforts, these new strategies strive to increase the tensile ductility while increasing/maintaining the strength simultaneously. In addition, the influence of tensile testing conditions, including strain rate, tensile specimen size and geometry, and strain measurement methods, on tensile ductility of NS materials was reviewed.